Household and agricultural roles of women in Barangay Kapatagan, Digos City, Davao del Sur - Estrada, Jhoana Myla A.
This study focused on the purposely-selected members of Kapatagan Livelihood Development Cooperative (KALIDECO) or wife of the cooperative members. There are fifty respondents in this study and all are residents of Barangay Kapatagan, Digos City, Davao del Sur. This study aims to: (1) know the different roles of women in household and farming; (2) find out if these women are just playing a 'helping out' role in their household and agriculture; and (3) find out if they experience multi-tasking roles. Since revealed that women play different roles in the household and agriculture. In the household, women are expected to wash the dishes, clean the house, wash and iron the clothes. Take care of the needs of the children and husband, buy the grocery needed for the house, look after the sari-sari store, prepare and cook the food and also budget the money. Moreover, women also plays different roles in agriculture such as weeding, plowing the land, planting and harvesting the crop, applying fertilizers and pesticides, selling the product to the metro, managing the farm and preparing the snack of the laborers. Furthermore, about thirty five of the respondents said that they also work as a laborer on other people's land to make their ends meet. Given such results, it is then concluded that women are not only playing the 'helping out' roles in the household and agriculture instead they are actually the primary movers.